Local Knowledge and Conservation of Seagrasses in the Tamil Nadu State of India - Newmaster AF; Berg KJ; Ragupathy S; Palanisamy M; Sambandan K; Newmaster SG (BMC, 2011)
Abstract Local knowledge systems are not considered in the conservation of fragile seagrass marine ecosystems. In fact, little is known about the utility of seagrasses in local coastal communities. This is intriguing given that some local communities rely on seagrasses to sustain their livelihoods and have relocated their villages to areas with a rich diversity and abundance of seagrasses. The purpose of this study is to assist in conservation efforts regarding seagrasses through identifying Traditional Ecological Knowledge (TEK) from local knowledge systems of seagrasses from 40 coastal communities along the eastern coast of India. We explore the assemblage of scientific and local traditional knowledge concerning the 1. classification of seagrasses (comparing scientific and traditional classification systems), 2. utility of seagrasses, 3. Traditional Ecological Knowledge (TEK) of seagrasses, and 4. current conservation efforts for seagrass ecosystems. Our results indicate that local knowledge systems consist of a complex classification of seagrass diversity that considers the role of seagrasses in the marine ecosystem. This fine-scaled ethno-classification gives rise to five times the number of taxa (10 species = 50 local ethnotaxa), each with a unique role in the ecosystem and utility within coastal communities, including the use of seagrasses for medicine (e.g., treatment of heart conditions, seasickness, etc.), food (nutritious seeds), fertilizer (nutrient rich biomass) and livestock feed (goats and sheep). Local communities are concerned about the loss of seagrass diversity and have considerable local knowledge that is valuable for conservation and restoration plans. This study serves as a case study example of the depth and breadth of local knowledge systems for a particular ecosystem that is in peril. Key words: local health and nutrition, traditional ecological knowledge (TEK), conservation and natural resources management, consensus, ethnomedicine, ethnotaxa, cultural heritage